ADVANCED SYSTEM FOR TECHNOLOGICAL PROCESS CONTROL - Dusan Nascak; Jan Kerekanic; Martina Husarova (European Scientific Journal, ESJ, 2013)
Industrial furnaces belong to the basic thermal apparatuses for material processing in many industry branches. The model based predictive control is the most suitable control approach. Developed control system consists of three level hierarchies. At the optimization level optimal control trajectory and its responding controls are determined at the time of material charging. At the discharging time period the model is calibrated, and real process trajectory is determined. The difference of optimal and real control trajectory used for the control correction at the stabilization level. Process monitoring and control of individual loops are executed at the basic level. Control interval is set according the difference of optimal and actual process trajectory. The simulation model is based on the first principles and enables real time simulation. Optimal working point can be determined according selected performance criteria which includes technical, technological, economic and environmental indexes. Control system is visual promoted. Visual support enables internal view to the furnace and it is oriented on the extraction of critical process and equipment parameters. Developed model based on predictive control system was applied on the rotary furnace of magnesia sintering at SMZ Jelsava, Slovakia.